Health day at the university of Namibia 2014 : A community service - Nauiseb, Taimi; Kloppers, Joan.M (International Journal of Medicine, 2016)
Although there are many ‘health days’ to promote important public health issues, many of which are supported by different institutions. Global public health campaigns offer great potential to raise awareness and understanding about health issues. There are many world days observed throughout the year related to specific health issues or conditions.The School of Public Health conducted yearly a health day in the beginning of March or April of each year. According to Clinicians handbook (1998) explains check -up as a clinical preventive services usually delivered by primary health care clinicians to persons with no signs and symptoms of illness as part of a routine health care process. Central to the periodic health examination.